Understanding the learning experiences of developmental math students - Lawrence, Eric (Kansas State University, 2019)
Developmental math education is designed to offer a pathway to college-level subject readiness. Existing research in developmental math education has evidenced success stories while also revealing opportunities for improvement. Prior studies have focused on issues of self-efficacy and have also contended with not only what helps students learn better, but also how this learning should be measured in the first place. Increasing external pressures from politicians and business interests underscore the need for greater understanding of how developmental math students can learn more effectively. The research question for this study is: How do developmental math students experience learning in their developmental math coursework? Rather than beginning with an existing theory of how these students learn, this study used a grounded theory methodology to develop a framework from the students’ descriptions of their experiences. Data was collected over two phases. The first phase was a brief online survey that served as a baseline for discovering relevant themes. These formed the basis for questions in the extended individual interviews for the second phase of data collection. In vivo, axial, and focused coding were used to create the emergent framework for how developmental math students learn. The survey identified themes of course engagement, affective teacher qualities, course structure, and student positionality as meaningful for the students. Analysis of the interviews led to the resultant theory that the students’ experiences were fundamentally influenced by the students’ ability to receive one-on-one help, their perception of their instructors’ willingness to help, and the extent to which their courses provided a supportive structure to organize the learning. Implications, limitations, and opportunities for further research are discussed as well.
Keywords: Developmental math; Student experience; College math; One-on-one help; Instructor willingness to help; Supportive structure